Diversity of the Fern and Fern-Allies of Goa in Western Ghats, India - V.S, Manickam; A, Benniamin; S, Harikrishnan (Malaysian Journal of Science, 2004)
The paper records of 51 species of Pteridophytes (47 ferns and 4 fern allies) belonging to 32 genera under 27 families collected from the hill ranges of Goa, Western Ghats, India. The list of ferns and fern allies includes notes on ecology, locality, note and uses etc. have been given.